Social Yes; Contract No - Hardin, Russell; Justus Liebig University Giessen (My University, 2014)
Social contract theory is incoherent and it does not work as desired. Among the most obvious disanalogies is that contracts are enforced by a third party, commonly the state. There is no such external enforcer for a constitution. Contractarian theorists typically ignore all such issues and use the metaphor of contract very loosely to ground a claim that citizens are morally obligated to defer to government by their consent, as the parties to a standard legal contract would be legally obligated. David Hume's term is acquiescence. He compellingly argues that actual citizens do not believe their own legal or political obligations depend on their having agreed to their social order. More often than not our interests are simply better served by acquiescing in the rules of that constitution than by attempting to change it. The forms of commitment that are important for constitutional and even for much of conventional social choice are those that derive from the difficulties of collective action to re-coordinate on new rules. They are inherent in the social structure of the conventions themselves, a structure that often more or less automatically exacts costs from anyone who runs against the conventions without anyone or any institution having to take action against the rule breaker. Establishing a constitution is itself a massive act of coordination that, if it is stable for a while, spawns conventions that depend for their maintenance on their self-generating incentives and expectations and that block alternatives.
Keywords: Consent; political obligation; contractualism; dual-convention; David Hume; coordination; acquiescence; Thomas Hobbes; John Rawls; ddc:100; ddc:330